Drought and heatwave impacts on semi-arid ecosystems' carbon fluxes along a precipitation gradient. (26th October 2020) - El-Madany, Tarek S.; Carrara, Arnaud; Martín, M. Pilar; Moreno, Gerardo; Kolle, Olaf; Pacheco-Labrador, Javier; Weber, Ulrich; Wutzler, Thomas; Reichstein, Markus; Migliavacca, Mirco
Abstract : The inter-annual variability (IAV) of the terrestrial carbon cycle is tightly linked to the variability of semi-arid ecosystems. Thus, it is of utmost importance to understand what the main meteorological drivers for the IAV of such ecosystems are, and how they respond to extreme events such as droughts and heatwaves. To shed light onto these questions, we analyse the IAV of carbon fluxes, its relation with meteorological variables, and the impact of compound drought and heatwave on the carbon cycle of two similar ecosystems, along a precipitation gradient. A four-year long dataset from 2016 to 2019 was used for the FLUXNET sites ES-LMa and ES-Abr, located in central (39°56'25″ N 5°46'28″ W) and southeastern (38°42'6″ N 6°47'9″ W) Spain. We analyse the physiological impact of compound drought and heatwave on the dominant tree species, Quercus ilex. Our results show that the gross primary productivity of the wetter ecosystem was less sensitive to changes in soil water content, compared to the dryer site. Still, the wetter ecosystem was a source of CO2 each year, owing to large ecosystem respiration during summer; while the dry site turned into a CO2 sink during wet years. Overall, the impact of the summertime compound event on annual CO2 fluxes was marginal at both sites, compared to drought events during spring or autumn. This highlights that drought timing is crucial to determine the annual carbon fluxes in these semi-arid ecosystems. This article is part of the theme issue 'Impacts of the 2018 severe drought and heatwave in Europe: from site to continental scale'.